Sustaining the utility and functionality of Community-Based Projects: a case study of Atwima Mponua District. - Yeboah, Kwabena (2021)
A thesis submitted to the Department of Construction Technology and Management, Kwame Nkrumah University of Science and Technology in partial fulfillment of the requirements for the award of Master of Science in Project Management.